2005
DOI: 10.1088/0305-4470/38/7/014
|View full text |Cite
|
Sign up to set email alerts
|

Quantum estimation for non-differentiable models

Abstract: State estimation is a classical problem in quantum information. In optimization of estimation scheme, to find a lower bound to the error of the estimator is a very important step. So far, all the proposed tractable lower bounds use derivative of density matrix. However, sometimes, we are interested in quantities with singularity, e.g. concurrence etc. In the paper, lower bounds to a Mean Square Error (MSE) of an estimator are derived for a quantum estimation problem without smoothness assumptions. Our main ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The state consequently changes into an orthogonal state with a different number of particles. This non-smooth change is in contrast with the assumptions upon which the standard quantum Cramér-Rao bound (5) is based, and requires the generalization to non-differentiable models [59]. However, this gives an intuition for the divergence of (F…”
Section: A Homogeneous Ideal Gasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The state consequently changes into an orthogonal state with a different number of particles. This non-smooth change is in contrast with the assumptions upon which the standard quantum Cramér-Rao bound (5) is based, and requires the generalization to non-differentiable models [59]. However, this gives an intuition for the divergence of (F…”
Section: A Homogeneous Ideal Gasesmentioning
confidence: 99%
“…Quantum estimation theory for non-differentiable models [59] needs to be applied when the temperature is exactly zero, as discussed in the appendix B.…”
Section: B Harmonically Trapped Ideal Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDF of ℘ t0,t|m is upper bounded by J t0 . When the PDF of ℘ t0,t|m is differentiable with respect to t, equality in (25) holds if and only if ℘ t0,t|m is the normal distribution with average zero and variance J −1 t0 .…”
Section: The Limiting Distribution Satisfies the Relationmentioning
confidence: 99%
“…In particular, no previous study showed the validity of the Holevo bound under the weaker condition of local asymptotic covariance in the multiparameter scenario. To avoid employing the (local) unbiasedness condition, we focus on the discretized version of the RLD Fisher information matrix, introduced by Tsuda and Matsumoto [25]. Using this version of the RLD Fisher information matrix, we manage to handle the local asymptotic covariance condition and to show the validity of the Holevo bound in this broader scenario.…”
Section: Introductionmentioning
confidence: 99%